2014
DOI: 10.1021/je500231c
|View full text |Cite
|
Sign up to set email alerts
|

Solubilities of Succinic Acid in Acetic Acid + Water Mixtures and Acetic Acid + Cyclohexane Mixtures

Abstract: The solubilities of succinic acid in acetic acid + water solvent mixtures at (303.2 to 333.2) K and acetic acid + cyclohexane solvent mixtures at (303.2 to 343.2) K were determined. It was found that the solubility of succinic acid in acetic acid + cyclohexane mixtures increases with increasing mass fraction of acetic acid at constant temperature. However, for the system of acetic acid + water solvent mixtures, acetic acid with the mass fraction of 0.20 shows the best dissolving capacity for succinic acid. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 14 publications
11
35
0
Order By: Relevance
“…To verify the accuracy and reliability of the experimental apparatus and experimental method, the determined solubility of AA and SA in cyclohexanone and HAc would be compared with the published data reported. [13][14][15][16][17]19,21,23 As shown in Figures 2 to 5 and Table 2, the experimental measured solubility was in good agreement with the available literature reported data, which indicates the accuracy and reliability of our experimental technique. 3 and summarized in Figures 6 and 7, in which ω 1 is the mass fraction of GA in GA + cyclohexanone and GA + HAc solvents and x represents the mole fraction solubility of AA in solvent mixtures.…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…To verify the accuracy and reliability of the experimental apparatus and experimental method, the determined solubility of AA and SA in cyclohexanone and HAc would be compared with the published data reported. [13][14][15][16][17]19,21,23 As shown in Figures 2 to 5 and Table 2, the experimental measured solubility was in good agreement with the available literature reported data, which indicates the accuracy and reliability of our experimental technique. 3 and summarized in Figures 6 and 7, in which ω 1 is the mass fraction of GA in GA + cyclohexanone and GA + HAc solvents and x represents the mole fraction solubility of AA in solvent mixtures.…”
Section: Methodssupporting
confidence: 83%
“…Comparisons between Experimental Solubility of AA, SA in Pure Cyclohexanone, and HAc with the Reported Data in Literatures at Pressure p = 101.3 kPa a,[13][14][15][16][17]19,21,23 …”
mentioning
confidence: 99%
“…This is common behavior among vitamins as observed in the literature 7 . Additionally, it is observed that thiamine solubility also increases with increasing temperature, as observed in the literature 7,[12][13][14] . An adequate relationship between the experimental results and the results described by the fitting models was observed.…”
Section: Resultsmentioning
confidence: 52%
“…Jiang measured the solubilities of SA in methanol + water mixtures and ethanol + water mixtures at the temperature range of 278.15–333.15 K . Song measured the solubilities of SA in acetic acid + water mixtures at the temperature range of 303.2–333.2 K and acetic acid + cyclohexane mixtures at the temperature range of 303.2–343.2 K . Luo measured the solubilities of AA, GA, and SA in acetic acid + cyclohexanone mixtures at the temperature range of 298.55–340.85 K …”
Section: Introductionmentioning
confidence: 99%
“…Some relevant solubilities of AA, GA, and SA in pure or mixed solvents could be obtained in recent literatures. Luo measured the solubilities of AA in acetic acid + ε-caprolactone mixtures and cyclohexanone + ε-caprolactone mixtures at the temperature range of 305.55 to 345.15 K. 12 Suren measured the solubilities of AA in various solvents, such as water, acetic acid, acetic acid + water solvent mixtures, cyclohexanol + cyclohexanone solvent mixtures at temperatures ranging from 303.0 to 403.0 K. 13 Li measured the solubilities of AA in GA + acetone solvent mixtures at temperatures ranging from 304.70 to 354.65 K and SA in GA + acetone solvent mixtures at the temperatures ranging from 284.95 to 316.35 K. 14 Shen measured the solubilities of AA in acetic acid + water solvent mixtures and acetic acid + cyclohexane solvent mixtures at temperatures ranging from 303.2 to 343.2 K. 15 Mao measured the solubilities of AA in different solvents, such as water, ethanol, chloroform, n-butanol, and acetone at the temperature range of 288.05−360.05 K. 16 Fan measured the solubilities of AA in several solvents, such as cyclohexanone, cyclohexanol, acetic acid, N,N-dimethylformamide, dimethylacetamide, and dimethyl sulfoxide at the temperature range of 290.80−355.15 K. 17 Shen measured the solubilities of AA in cyclohexanone + cyclohexanol mixtures at the temperature range of 303.15−349.45 K, cyclohexane + cyclohexanol mixtures at the temperature range of 304.15−339.45 K, and cyclohexane + cyclohexanone mixtures at the temperature range of 304.85−342.45 K. 18 Yu measured the solubilities of AA in cyclohexanol + cyclohexanone solvent mixtures at the temperature range of 303.0−353.0 K and cyclohexanone + cyclohexane solvent mixtures at the temperature range of 303.0−378.5 K. 19 Gaivoronskii measured the solubilities of AA in methanol at the temperature range of 273.2− 333.2 K. 20 Lei measured the solubilities of GA in acetic acid + water mixtures at the temperature range of 303.2−333.2 K and acetic acid + cyclohexane mixtures at the temperature range of 303.2−343.2 K. 21 Song measured the solubilities of GA in cyclohexanone + cyclohexanol mixtures and acetic acid at the temperature range of 292.15−354.60 K. 22 Jiang measured the solubilities of SA in methanol + water mixtures and ethanol + water mixtures at the temperature range of 278.15−333.15 K. 23 Song measured the solubilities of SA in acetic acid + water mixtures at the temperature range of 303.2−333.2 K and acetic acid + cyclohexane mixtures at the temperature range of 303.2− 343.2 K. 24 Luo measured the solubilities of AA, GA, and SA in acetic acid + cyclohexanone mixtures at the temperature range of 298.55−340.85 K. 25 Unfortunately, satisfactory experimental equilibrium data for AA, GA, and SA in DMA + methanol solvent mixtures are lacking for the particular conditions of temperature and composition required in a particular program. Hence, it is essential to measure and correlate the solubilities of AA, GA, and SA in DMA + methanol solvent mixtures, respectively.…”
Section: Introductionmentioning
confidence: 99%